2013
DOI: 10.1371/journal.ppat.1003128
|View full text |Cite
|
Sign up to set email alerts
|

The Apoptogenic Toxin AIP56 Is a Metalloprotease A-B Toxin that Cleaves NF-κb P65

Abstract: AIP56 (apoptosis-inducing protein of 56 kDa) is a major virulence factor of Photobacterium damselae piscicida (Phdp), a Gram-negative pathogen that causes septicemic infections, which are among the most threatening diseases in mariculture. The toxin triggers apoptosis of host macrophages and neutrophils through a process that, in vivo, culminates with secondary necrosis of the apoptotic cells contributing to the necrotic lesions observed in the diseased animals. Here, we show that AIP56 is a NF-κB p65-cleaving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
87
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(95 citation statements)
references
References 92 publications
5
87
0
Order By: Relevance
“…Interestingly, AIP56 seems to have originated from a fusion of two components: one related to NleC, which is a type III secreted effector present in several enteric pathogenic bacteria (14) associated with human illness and death worldwide (15), and another related to a protein of unknown function from the bacteriophage APSE2. In line with this, we recently found that AIP56 is an AB-type toxin, possessing a catalytic A domain at its N terminus, homologous to NleC, and a B domain involved in binding/internalization into target cells at its C-terminal region, homologous to APSE2 (16). The catalytic domain of AIP56 is a zinc-dependent metalloprotease that, similarly to NleC, cleaves NF-B, an evolutionarily conserved transcription factor that regulates the expression of inflammatory and anti-apoptotic genes, playing a key role in host responses to microbial pathogen invasion (17).…”
supporting
confidence: 52%
See 4 more Smart Citations
“…Interestingly, AIP56 seems to have originated from a fusion of two components: one related to NleC, which is a type III secreted effector present in several enteric pathogenic bacteria (14) associated with human illness and death worldwide (15), and another related to a protein of unknown function from the bacteriophage APSE2. In line with this, we recently found that AIP56 is an AB-type toxin, possessing a catalytic A domain at its N terminus, homologous to NleC, and a B domain involved in binding/internalization into target cells at its C-terminal region, homologous to APSE2 (16). The catalytic domain of AIP56 is a zinc-dependent metalloprotease that, similarly to NleC, cleaves NF-B, an evolutionarily conserved transcription factor that regulates the expression of inflammatory and anti-apoptotic genes, playing a key role in host responses to microbial pathogen invasion (17).…”
supporting
confidence: 52%
“…The catalytic domain of AIP56 is a zinc-dependent metalloprotease that, similarly to NleC, cleaves NF-B, an evolutionarily conserved transcription factor that regulates the expression of inflammatory and anti-apoptotic genes, playing a key role in host responses to microbial pathogen invasion (17). We have shown that during intoxication of sea bass peritoneal leukocytes (sbPL), the catalytic activity of AIP56 results in the depletion of NF-B p65 (16), and this likely explains the disseminated apoptosis observed during P. damselae subsp. piscicida infections.…”
mentioning
confidence: 99%
See 3 more Smart Citations